A textbook of engineering mechanics : applied mechanics - Khurmi, R.S (S. Chand and Co, 2004)
A textbook of engineering mechanics : applied mechanics / Khurmi, R.S. -- New Delhi: S. Chand and Co, 2004 620.1 K45e19 19th ed. No. of Copies : 1